2016
DOI: 10.1016/j.jbiomech.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear scaling of a musculoskeletal model of the lower limb using statistical shape models

Abstract: Accurate muscle geometry for musculoskeletal models is important to enable accurate subject-specific simulations. Commonly, linear scaling is used to obtain individualised muscle geometry. More advanced methods include non-linear scaling using segmented bone surfaces and manual or semi-automatic digitisation of muscle paths from medical images. In this study, a new scaling method combining non-linear scaling with reconstructions of bone surfaces using statistical shape modelling is presented. Statistical Shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 19 publications
(20 reference statements)
1
46
1
Order By: Relevance
“…This indicates that the linear scaling based on the gender and anthropometric similarity may not be adequate, especially for the hip joint force prediction. Recent studies have demonstrated a better estimation of muscle attachment sites by applying a morphing technique to the bone surface when compared to linear scaling [54], [55]. This technique could in future be applied to generate a larger, population-based dataset of subject-specific musculoskeletal models.…”
Section: Table V Correlation Between Root Mean Square Difference (Rmsmentioning
confidence: 99%
“…This indicates that the linear scaling based on the gender and anthropometric similarity may not be adequate, especially for the hip joint force prediction. Recent studies have demonstrated a better estimation of muscle attachment sites by applying a morphing technique to the bone surface when compared to linear scaling [54], [55]. This technique could in future be applied to generate a larger, population-based dataset of subject-specific musculoskeletal models.…”
Section: Table V Correlation Between Root Mean Square Difference (Rmsmentioning
confidence: 99%
“…Incomplete bone models, however, may represent an obstacle to the identification of the muscle attachments when the aim is generating a complete musculoskeletal model. This issue can be solved by combining the STAPLE toolbox with a statistical shape workflow to reconstruct entire bone geometries from sparse datasets (Nolte et al, 2016;Suwarganda et al, 2019). It is worth mentioning that, although statistical shape modelling workflows present the advantage of reconstructing bone geometries from sparse segmentations or even skin landmarks, bone models from medical image segmentation still provide the most accurate estimations of joint parameters; for example, median root-mean-squared errors up to 11.09 mm and larger than 13.8 mm (Nolte et al, 2020) have been reported in the identification of the centre of the femoral head using statistical shape models.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical shape modelling workflows have recently demonstrated high potential for reconstructing bone geometries from sparse anatomical datasets (Davico et al, 2019;Nolte et al, 2016;Suwarganda et al, 2019) and landmarks digitized in the gait lab (Nolte et al, 2020;Zhang et al, 2016), but to the best of the authors' knowledge they do not yet offer methods to generate articulated skeletal models of the complete lower limb. The bone reconstructions are limited to the long bones (Nolte et al, 2020;Nolte et al, 2016) or omit the talus and foot bones (Davico et al, 2019;Suwarganda et al, 2019;Zhang et al, 2016), and in musculoskeletal modelling contexts they have been employed to perform non-linear scaling of pre-existing muscle attachments (Nolte et al, 2016) with scarce focus towards joint modelling. Hence, a comprehensive approach to generate entire lower limb models from personalised bone geometries is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Computational approaches to study the correlation between morphological features and functional or pathological conditions of bony surfaces using SSM have been emerging in the literature, with impacts in biomechanics, especially for kinematic and dynamic analysis (Rao et al, 2013;Smoger et al, 2015;Nolte et al, 2016;Zhang et al, 2016;Hollenbeck et al, 2018;Clouthier et al, 2019), and clinics, especially for diagnostic and surgical interests MoV/p value HKA 5 (p = 0.0001), 7 (p = 0.03), 17 (p = 0.02), 18 (p = 0.03) FVV 5 (p = 0.001), 10 (p = 0.01), 17 (p = 0.01) IER 2 (p = 0.02) TVV 11 (p = 0.008), 14 (p = 0.01), 16 (p = 0.01), 17 (p = 0.03) TS 5 (p = 0.02) (Neogi et al, 2013;Peloquin et al, 2014;Mutsvangwa et al, 2015;Cerveri et al, 2018). In particular, three studies addressed the relation between SSM parameters and knee kinematics by focusing on the link between the morphological variability of the bones and tibio-femoral alignment modifications (Rao et al, 2013;Smoger et al, 2015;Clouthier et al, 2019).…”
Section: Findings Limitations and Possible Developmentsmentioning
confidence: 99%